ANALISA FAKTOR MAKRO EKONOMI TERHADAP RETURN ON ASSET PERBANKAN SYARIAH - Silviana Pebruary; Shalihul Aziz Widya Irawan (FEBI IAIN Langsa, 2017)
This study aims to analyze the macroeconomic factors (inflation, BI rate, Domestic Product Growth) that influence Return on Asset (ROA) in Islamic banking. The population of this study was Islamic bank registered in Indonesian Bank 2009-2016, which is Mandiri syariah banking. The purposive sampling method by selecting the bank’s financial reports quarterly was used as the technique of data collection. The data then was analyzed by using the classical assumption test, multiple regression analysis, and hypothesis testing using software tools Eviews.5.1. The result showed that inflation, BI rate, and the Growth of Domestic Product had an effect on ROA. In particular, inflation had positive effect towards ROA, but BI rate and the Growth of Domestic Product showed negative one.